2020
DOI: 10.3390/coatings10090875
|View full text |Cite
|
Sign up to set email alerts
|

On-Aluminum and Barrier Anodic Oxide: Meeting the Challenges of Chemical Dissolution Rate in Various Acids and Solutions

Abstract: The chemical dissolution—in 0.1 M solutions of phosphoric, malonic, citric, sulfosalicylic, and tartaric acids and 0.6 M solutions of sulfuric, oxalic, malonic, phosphoric, tartaric, and citric acids—of aluminum (Al) and its barrier anodic oxide, with thicknesses of 240 and 350 nm, produced during the anodization of Al deposited on a sitall substrate and Al foil, respectively, in a 1% citric acid aqueous solution, was investigated. Signs of chemical dissolution for 0.1 M phosphoric acid solution and 0.6 M conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Secondly, the electrolyte and the PAF outer layer interact chemically, which leads to partial etching of the PAF. At low current densities in aggressive electrolytes such as SA [ 64 ], the aluminum oxidation rate is low, the contact time with electrolytes is long, and the dissolution rate is comparable to the oxidation rate. A sharp decrease of K g at long contact times (low anodic current densities) as observed here, also according to the data of ref.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the electrolyte and the PAF outer layer interact chemically, which leads to partial etching of the PAF. At low current densities in aggressive electrolytes such as SA [ 64 ], the aluminum oxidation rate is low, the contact time with electrolytes is long, and the dissolution rate is comparable to the oxidation rate. A sharp decrease of K g at long contact times (low anodic current densities) as observed here, also according to the data of ref.…”
Section: Resultsmentioning
confidence: 99%
“…This may yield a certain degree of discrepancies as initial geometric features are determined by the process conditions. The dissolution rate of NAA in various acids is compared in the work of Poznyak et al [ 31 ]. It was demonstrated to depend on the nature of the acid—the reactivity with respect to aluminum and the morphology of aluminum surface.…”
Section: Nanoporous Anodic Alumina (Naa): Definition and Formationmentioning
confidence: 99%
“…The combined anodizing time response of both non-hydrogenated and hydrogenated Ti deposited on silicon wafers in a 1% TA solution is shown in Figure 2a. It can be observed that the profile for anodizing non-hydrogenated Ti corresponds to the descriptions for the cases of obtaining a barrier oxide layer on Al and other valve metals [7,[92][93][94][95][96][97]. At the same time, the anodizing time response of the hydrogenated samples significantly differed from the reference sample.…”
Section: Anodizing In Tartaric Acidmentioning
confidence: 68%